Leadership Development Strategies and Organizational Culture: Leadership Development Strategies and Organizational Culture (Impact: Journal of Transformation, 2022)
This study sought to determine how leadership development strategies affect organizational culture in the context of the Care For Aids Organization. Leaders widely agree that sustained organizational performance is highly influenced by organizational culture. Organizations are always looking for ways of nurturing desirable organizational cultures. As much as leaders recognize the importance of organizational culture, they spend less time, effort, and resources in cultivating the desired culture. The specific study objectives were to determine how coaching programs affect organizational culture, establish how training programs affect organizational culture, assess how mentoring affects organizational culture, and examine how transformational leadership style affects organizational culture. A descriptive research design was used, and a census study targeted all 66 administrative staff within Care For Aids. The researcher used Mentimeter, a web-based platform for administering the five-point Likert scale questionnaire. The correlation analysis shows significant associations between the proposed predictors and the independent variable, which was further tested using regression analysis. From the regression coefficient, the main predictors of organizational culture are transformational leadership (coef: 0.475, p=0.00) and training (coef: 0.222, p=0.09). Although there were associations between mentoring and coaching as potential predictors of organizational culture in the correlation analysis, these associations do not appear to be statistically significant when regression modeling is conducted. The study recommends that the management of Care For Aids invest in nurturing and promoting a strong and desirable organizational culture through increased training and mentoring programs and lead through a transformational leadership style.